Salivary levels of HNP 1-3 are related to oral ulcer activity in Behcet's disease - MUMCU, GONCA; DİRESKENELİ, RAFİ HANER; ERGUN, SAFİYE ATLAS TÜLİN; CİMİLLİ, ZÜHRE HALE (WILEY, 2013)
Background Saliva contains antimicrobial peptides derived from oral epithelium as well as neutrophils in the innate immune response. The aim of this study was to examine the association between salivary human neutrophil peptide (HNP) 1-3 levels originating from neutrophils and oral ulcers in patients with Behcet's disease (BD). Methods Ninety-five patients with BD (F/M: 39/56; mean age: 38.711.9years) and 53 healthy controls (HC; F/M: 23/30; mean age: 35.210.1years) were included in the study. The disease control group (F/M: 20/33; mean age: 33.7 +/- 10.7years) was comprised of patients with oral infection regarding endodontic infection (n=32) and pericoronitis (n=21). Salivary HNP 1-3 levels of groups were measured in unstimulated samples by ELISA (Hycult, the Netherlands). Results A statistically significant increase was found in salivary HNP 1-3 levels of patients with BD (2268.28 +/- 1216.38g/ml) compared with HC (1836.49 +/- 857.76g/ml), patients with endodontic infection (849.9 +/- 376.1g/ml), and patients with pericoronitis (824.3 +/- 284.02g/ml; P=0.024, 0.000 and 0.000, respectively). The ratio of active oral ulcer (100%, n=14) was higher in low HNP 1-3 levels (1000g/ml) than the others (66.7%, n=54) in active patients with BD (P=0.008). Moreover, salivary HNP 1-3 levels were significantly lower in patients with endodontic infection and patients with pericoronitis compared with those in the HC group and patients with BD (P=0.000). Conclusion A decrease in salivary HNP 1-3 levels might be a biological factor for predisposition to oral ulcers in patients with BD and oral infection in healthy patients.
Keywords: ANTIMICROBIAL PEPTIDE; DEFENSINS; EXPRESSION; CRITERIA; HEALTH